Linear and Non-linear Correlations Between Serum Phosphate Level and Bone Mineral Density in Type 2 Diabetes - Yang, Yinqiu; Liu, Guangwang; Zhang, Yao; Xu, Guiping; Yi, Xilu; Liang, Jing; Zhao, Chenhe; Liang, Jun; Ma, Chao; Ye, Yangli; Yu, Mingxiang; Qu, Xinhua (Frontiers in Endocrinology, 2020)
Introduction: Serum phosphate plays an important role in bone mineralization and might be a risk factor for many bone diseases. Patients with T2D usually have low serum phosphate level due to diet control, osmotic diuresis and insulin stimulation. Current studies have discussed the linear association between serum phosphate and bone mineral density (BMD). Objective: We aimed to analyze both the linear and nonlinear correlations between serum phosphate and BMD in patients with type 2 diabetes (T2D). Methods: We included 1469 patients with T2D and obtained their basic information, laboratory measurements, and BMD data. Multivariate adjusted linear regression was used to analyze the linear associations, and we applied a two-piecewise linear regression model using a smoothing function to examine the nonlinear association. Results: No linear correlation was found between serum phosphate and BMD in patients with T2D. In women with T2D, we found a nonlinear correlation between serum phosphate level and femur neck or total hip BMD. When serum phosphate was <1.3 mmol/L, it was positively associated with femur neck and total hip BMD, whereas when phosphate was >1.3 mmol/L, it was negatively associated with femur neck BMD. Conclusions: In men with T2D, serum phosphate level was not associated with BMD. However, in women with T2D, we found a nonlinear correlation between serum phosphate and femur neck or total hip BMD.